The Market Moves Us in Mysterious Ways: DeLillo’s Critique of Transnationalism in Cosmopolis - Cvek, Sven (Array, 2002)
The article analyzes the forces influencing what some authors see as the "deterritorialization" of American literature and national identity. The article's thesis is that Don DeLillo's novel Cosmopolis finctions as a contemporary exploration of the deterritorializing power of capital on the American national imaginary.